2014
DOI: 10.1021/jf502835n
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Degradation of Cypermethrin and Its Metabolite, 3-Phenoxybenzoic Acid, by the Cooperation of Bacillus licheniformis B-1 and Sphingomonas sp. SC-1

Abstract: Cypermethrin (CY) and its metabolite, 3-phenoxybenzoic acid (3-PBA), generally coexist in agricultural soil and cause a toxic effect on the human body. In this study, CY and its metabolite 3-PBA were simultaneously degraded by the cooperation of Bacillus licheniformis B-1 and Sphingomonas sp. SC-1. The effects of the inoculation proportion and inoculation method of these two strains, cultivation time, and initial CY content on the degradation of CY and 3-PBA were investigated. Furthermore, the degradation of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 30 publications
(56 reference statements)
3
70
0
Order By: Relevance
“…The results suggested that the presence of graphene might have a negative impact on the cycling of nitrogen, and further research should be performed to explore the influence of graphene on the specific microbial communities or functional genes that are responsible for nitrogen cycling. The genera Arthrobacter, Geobacter and Bacillus are commonly described as being capable of degrading organic pollutants [46][47][48], which is very useful for bioremediation. The results of the present study indicated the positive impact of graphene on these populations, suggesting that graphene may be considered to act as a promoter of the degradation of organic pollutants and to improve the biodegradation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the presence of graphene might have a negative impact on the cycling of nitrogen, and further research should be performed to explore the influence of graphene on the specific microbial communities or functional genes that are responsible for nitrogen cycling. The genera Arthrobacter, Geobacter and Bacillus are commonly described as being capable of degrading organic pollutants [46][47][48], which is very useful for bioremediation. The results of the present study indicated the positive impact of graphene on these populations, suggesting that graphene may be considered to act as a promoter of the degradation of organic pollutants and to improve the biodegradation efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…LB-MS medium was prepared according to previously described methods [13] and consisted of LB and MS at a ratio of 2:1 (v/v). The pH value of medium was adjusted to between 7.0 and 7.5 prior to sterilization at 121°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…Bacillus licheniformis B-1 is capable of efficiently degrading β-CY via co-metabolism, but was unable to degrade 3-PBA [13]. Previous reports demonstrated that fungi are more efficient than bacteria in degrading compounds with benzene ring structures [15,16,19], implying that fungi should be more suitable to degrade 3-PBA as compared to bacteria [19].…”
Section: Introductionmentioning
confidence: 99%
“…Three gram-negative strains, including one strain of genus Sphingopyxis, are only capable of degrading geosmin when they are combined as a whole group (Hoefel et al, 2006). The emergent biochemical properties generated from interspecific interactions contribute to our general knowledge of single strain functions, and provide us with an alternative method to accomplish various tasks, such as identification of new fungi-derived pharmaceuticals (Bertrand et al, 2014;Ochi and Hosaka, 2013) and degradation of organic contaminants (Liu et al, 2014;Wu et al, 2010;Zhang et al, 2013). However, research regarding transformations of certain metals (e.g.…”
Section: Introductionmentioning
confidence: 99%